2022
DOI: 10.3390/ijms23020773
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Fermentation of Glucose and Glycerol for High-Yield N-Acetylglucosamine Production in Escherichia coli

Abstract: N-acetylglucosamine (GlcNAc) is an amino sugar that has been widely used in the nutraceutical and pharmaceutical industries. Recently, microbial production of GlcNAc has been developed. One major challenge for efficient biosynthesis of GlcNAc is to achieve appropriate carbon flux distribution between growth and production. Here, a synergistic substrate co-utilization strategy was used to address this challenge. Specifically, glycerol was utilized to support cell growth and generate glutamine and acetyl-CoA, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In E. coli cells, fructose-6-phosphate can also be phosphorylated into fructose-1, 6-bisphosphate by 6-phosphofructokinases ( pfkA , pfkB ) and utilized as a carbon source through the EMP pathway ( Wang et al, 2022 ). Therefore, blocking the phosphorylation of fructose-6-phosphate may favor the synthesis of D-allulose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In E. coli cells, fructose-6-phosphate can also be phosphorylated into fructose-1, 6-bisphosphate by 6-phosphofructokinases ( pfkA , pfkB ) and utilized as a carbon source through the EMP pathway ( Wang et al, 2022 ). Therefore, blocking the phosphorylation of fructose-6-phosphate may favor the synthesis of D-allulose.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4C, buffering LB medium with 100 mM potassium phosphate was able to limit this acidification to pH 5.7 after 72 h, and the D-allulose titer increased to 0.51 g/L, with depletion of 4.03 g/L D-fructose. In E. coli cells, fructose-6-phosphate can also be phosphorylated into fructose-1, 6-bisphosphate by 6phosphofructokinases (pfkA, pfkB) and utilized as a carbon source through the EMP pathway (Wang et al, 2022). Therefore, blocking the phosphorylation of fructose-6phosphate may favor the synthesis of D-allulose.…”
Section: Regulation Of Metabolic Pathways To Increase Cell Factory Ef...mentioning
confidence: 99%
“…The addition of GlcNAc in the salvage pathway increased the cost in LNB production, and it has been reported that GlcNAc can be generated via microbial fermentation (Table S5). Thus, the de novo pathway should be developed in K. lactis for synthesizing LNB using lactose as the sole substrate (without the addition of GlcNAc).…”
Section: Results and Discussionmentioning
confidence: 99%
“…E. coli can utilize glucose and glycerol as carbon sources to produce various chemicals. Significant production enhancement could be realized through synergetic utilization of glucose and glycerol, which has been successfully applied to many valuable chemical biosynthesis processes such as myo-inositol, 38 lycopene, 39 N-acetylglucosamine, 40 and so forth. To achieve higher salicin production, the optimization of medium was conducted by varying the carbon sources in modified M9Y medium.…”
Section: Resultsmentioning
confidence: 99%